(untitled) (Linguostylistic Studies, 2020)
The article deals with the analysis of the cosmonyms (sun and the related concepts, phenomena, and actions - rays, sky, darkness, dawn, dusk, sunset, sunrise, ghost, mist, evening star, constellations, moon), using as a case study the works by S. Vasylchenko, a native of Chernihiv region. The study has revealed the use of such artistic means as the metaphor, epithet, oxymoron, comparison, and their informational and aesthetic significance in the texts. Astronominations in the tropes are used mostly to reproduce pictures of nature, the surrounding reality, as well as to characterize the inner experiences, the appearance of the characters, to describe the events taking place around them. The author achieves expressiveness by conveying the essence of an object or phenomenon through the features of another on the basis of their similarity. Metaphorical images are created via the use of words in their figurative sense ("The sun warmed... kissed the boy....", "...looked out the edge of the moon from behind the cloud…"). Bright synonymous series of nouns ("star", "aurora", "girls-stars", "sunshine", "hedgehog in the sky", "ball", "crescent moon", "fire-bird", etc.), adjectives ("diamond", "evening", "shiny", "bright", "hot", etc.), verbs ("shines", "burns", "soars", "glows", "warms", "entertains", "bakes", "blazes", etc.) have been revealed. Epithets-coloratives are used to create the image of the moon ("silver", "pale", "gold", "yellow", "reddish", "white", etc.). Impersonal verb forms are actively used to add some mystery, uncertainty to the portrayed (e.g. “getting dark”). The study lays emphasis on the usage frequency of the astrolexemes in S. Vasylchenko’s works. The names of the sun and the concepts related to sunrise and sunset are the most numerous lexical-semantic groups. Most of the analyzed tokens are commonly used words inherent in the modern Ukrainian literary language, and the rest are the nouns used in dialects.